2018
DOI: 10.29375/01237047.2397
|View full text |Cite
|
Sign up to set email alerts
|

Determinación del poder corneal con un tomógrafo corneal luego de cirugía refractiva con láser excimer

Abstract: Introducción. La determinación del poder corneal, después de la cirugía refractiva con láser excimer, es difícil. Diferentes alternativas con el uso de tomógrafos corneales se han utilizado para esta medición. Objetivo. Evaluar diversos métodos de determinación del poder corneal en pacientes operados de cirugía fotorrefractiva, incluyendo pruebas diagnósticas con medidas cuantitativas. Metodología. Estudio retrospectivo de pacientes operados de cirugía fotorrefractiva que tuvieran resultados refractivos y tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Another study conducted by Jaramillo et al concluded that the corneal power obtained postoperatively from the Sirius® tomographer (Costruzione Strumenti Oftalmici CSO, Firenze, Italy), using the Mean Pupil Power (MPP) map, averaged either with the values of the postoperative manual keratometry or with the values of the postoperative Sirius® SimK, resulted in a corneal power which did not show a statistically significant difference when compared to the one obtained from the clinical history method [14]. This was due to the fact that the MPP generally underestimated postoperative corneal power by a value similar in magnitude to its overestimation generated by both postoperative manual keratometry and Sirius® postoperative SimK [14].…”
Section: Determination Of Corneal Power Post Refractive Surgerymentioning
confidence: 99%
“…Another study conducted by Jaramillo et al concluded that the corneal power obtained postoperatively from the Sirius® tomographer (Costruzione Strumenti Oftalmici CSO, Firenze, Italy), using the Mean Pupil Power (MPP) map, averaged either with the values of the postoperative manual keratometry or with the values of the postoperative Sirius® SimK, resulted in a corneal power which did not show a statistically significant difference when compared to the one obtained from the clinical history method [14]. This was due to the fact that the MPP generally underestimated postoperative corneal power by a value similar in magnitude to its overestimation generated by both postoperative manual keratometry and Sirius® postoperative SimK [14].…”
Section: Determination Of Corneal Power Post Refractive Surgerymentioning
confidence: 99%